Support By The Government To Smes In Indonesia - Lim Sanny, Patricia Noveli, Salsabila Aathirah Boekoesoe, Lea Simek (International Journal of Advanced Science and Technology, 2020)
SMEs play a big role in a country’s economic growth contributing employment. SMEs in Indonesiaface an array of issues inhibiting growth. The study investigates financial and educational forms of supportby the government to the SMEs. The Importance Performance Analysis method identifies what should beimproved, maintained, less focused on, and eliminated. The study sampled opinions from SME’s inIndonesia engaged in Arts and Crafts, Fashion, and Food and Beverage industries. 2-tailed t-tests indicatedsignificant differences between importance and performance scores. While the industries are generallyconfident in their management skills, they expect more support with development funding. Differences werefound between industries were also found.